Point A to B facilitating climate driven internal migration among small Filipino families moving from rural to urban settings - Orosa, Isabella Maria F.
Climate change has had an impact on the way people live and has shifted the demands and lifestyle of people. Large groups of people are migrating from their original location of residence both voluntarily and involuntarily to meet their needs. This is not exactly uncommon, and could be said to be a phenomenon taking place as indicated by the presences of rural migrants looking for means of livelihood. However, articles have not sufficiently addressed the movement brought about by slow onset climate changes and its effects on new Filipino families looking for a livelihood. While most are moving to look for better opportunities, pursue a sense of independence, climate events that affect livelihoods are a reason why migration can slowly become a more typical phenomenon. This project thus aims to explore architectural solutions to help small and young families cope with rapid urban changes in the context of migration from rural setting to urban settings. It mainly looks at the changes in the life of the small Filipino family and how architecture can facilitate that move with ease. In synthesizing these findings, climate migrants, apart from seeking greener pastures, face socio economic issues before migration and psychosocial as a result from moving from their homes. Thus, a mixed use community housing set-up integrated with urban agriculture strategies, climate technology underpinned by concepts of Biophilia is acknowledged to be an apt solution to tackle the inevitable migration from rural areas. It is hoped that this study can inform readers and design practitioners of the migrant movement and their plight as it happens under the context of climate change and the role of architecture in mediating that flow.